2018
DOI: 10.3389/fimmu.2018.02729
|View full text |Cite
|
Sign up to set email alerts
|

TCR Repertoire as a Novel Indicator for Immune Monitoring and Prognosis Assessment of Patients With Cervical Cancer

Abstract: There is increasing evidence that deep sequencing-based T cell repertoire can sever as a biomarker of immune response in cancer patients; however, the characteristics of T cell repertoire including diversity and similarity, as well as its prognostic significance in patients with cervical cancer (CC) remain unknown. In this study, we applied a high throughput T cell receptor (TCR) sequencing method to characterize the T cell repertoires of peripheral blood samples from 25 CC patients, 30 cervical intraepithelia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
100
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(107 citation statements)
references
References 38 publications
4
100
0
Order By: Relevance
“…Such impact has not been seen for OS, probably due to the small size of the cohort, but when we separated patients according to their early death or long survival, a significant association is visible, with a lower DR in patients who died early. In line with our data, in many tumor types, TCR repertoire diversity appears as a prognostic factor of clinical outcome in cancer patient, a high diversity being associated with a better prognosis (Cui et al, ; Jin et al, ; Keane et al, ; Lin et al, ; Manuel et al, ; Tamura et al, ). A high TCR repertoire diversity could reflect a good functionality of the immune system, increasing chances that a sub‐population immunologically pertinent should be present, leading therefore to a better anti‐tumor immune response.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Such impact has not been seen for OS, probably due to the small size of the cohort, but when we separated patients according to their early death or long survival, a significant association is visible, with a lower DR in patients who died early. In line with our data, in many tumor types, TCR repertoire diversity appears as a prognostic factor of clinical outcome in cancer patient, a high diversity being associated with a better prognosis (Cui et al, ; Jin et al, ; Keane et al, ; Lin et al, ; Manuel et al, ; Tamura et al, ). A high TCR repertoire diversity could reflect a good functionality of the immune system, increasing chances that a sub‐population immunologically pertinent should be present, leading therefore to a better anti‐tumor immune response.…”
Section: Discussionsupporting
confidence: 87%
“…In nasopharyngeal carcinoma, a lower diversity of TCR repertoire in tumors compared to paired tissues and a higher diversity in peripheral blood are associated with a poor prognosis (Jin et al, ). The diversity of circulating TCR repertoire is gradually decreasing during tumor progression in patients with cervical cancer (Cui et al, ). Elsewhere, high dominant clones within tumor microenvironment were associated with poor outcome in diffuse large B‐cell lymphoma (Keane et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…31,32 This implies that a preexisting T-cell-mediated immune response, reflected by local intratumoral TCR clonal expansion, would be a pre-requisite for successful treatment outcomes to these immunotherapies. In contrast, several studies have observed an opposite direction of the association between TCR repertoire diversity and treatment outcomes in other solid tumor types, 33,34 underscoring the complex interactions between the immune system and advanced malignancies. 35 This complexity notwithstanding, these reports also suggest the direct measurement of TCR repertoire diversity within tumors may be utilized to predict clinical immunotherapeutic efficacy.…”
Section: Discussionmentioning
confidence: 96%
“…As single-cell approaches move toward the precise quantification of rare cell types, trajectories, perturbations, and clones, an understanding of potential artifacts is essential as their confounding effects may become exacerbated in large datasets. Additionally, as these measurements move toward clinical applications 9 , particularly in tumors where TCR repertoire may serve as a prognostic biomarker 10 , barcode multiplets may significantly confound interpretation. In some analyses (with <15% clones), we anticipate that many identified clonal cells may arise from bead multiplets.…”
Section: Confounding Of Clonal Lymphocytes Due To Barcode Multipletsmentioning
confidence: 99%